Case study results from southeast Houston, Texas: identifying the impacts of residential location on flood risk and loss. (14th July 2015) - Brody, S.D.; Sebastian, A.; Blessing, R.; Bedient, P.B.
Abstract: Despite the increasing economic losses from floods in coastal communities, little observational research has been done at a fine spatial scale to identify the relative influence of residential location in predicting adverse economic impacts. In response, this study conducts a parcel‐level analysis of flood losses to identify the influence of specific location‐based variables on property damage from multiple flood events. We statistically isolate the effect of multiple location‐based characteristics on insured flood claims associated with two major coastal storms for over 7813 properties within the Clear Creek watershed southeast of Houston, Texas. Results indicate that location‐based variables are among the strongest predictors for both, where seemingly subtle shifts in location add up to large dollar losses from flooding. These findings provide an increased understanding of the role of physical location within a flood‐vulnerable region and how residential choice can be a major factor in exacerbating actual property loss.